REKONTEKSTUALISASI TEKNIK PENERJEMAHAN MOLINA DAN ALBIR DALAM KERANGKA TRANSKREASI: SEBUAH STUDI LITERATUR KONSEPTUAL - Nur Hasyim; Darul Nurjanah (Epigram, 2026)
ABSTRACT Transcreation has increasingly gained scholarly attention in translation studies, particularly in relation to persuasive texts, advertising, and cross-cultural communication; however, the theoretical relationship between transcreation as a macro-level orientation and translation techniques as micro-level procedures remains insufficiently systematized. This article aims to (1) elaborate the theoretical construction of transcreation drawing on Haroldo de Campos’ concept of Translation as Creation and Criticism and six Scopus-indexed journal articles within contemporary translation studies, and (2) identify which translation techniques proposed by Lucía Molina and Amparo Hurtado Albir potentially support transcreation practice. Employing a literature review method, this study analyzes key works on transcreation alongside Molina and Albir’s taxonomy through a comparative-conceptual approach to map the convergence between communicative-effect orientation and micro-textual procedures. The findings suggest that translation may be conceptualized as an aesthetically autonomous act of recreation and that not all techniques are equally compatible with transcreation; adaptation, modulation, amplification, and particularly discursive creation exhibit the greatest potential to enable shifts in meaning, perspective, and rhetorical strategy in achieving the intended communicative impact on target audiences. Keywords: transcreation, translation techniques, Molina and Albir, recontextualization, literature